Study on Emotional Intelligence among Sports Person and Non-Sports Person of Karnataka State Akkamahadevi Women’s University Vijayapura: A Comparative Study on Emotional Intelligence and Self-confidence among Female Sports Persons and Non-Sports Persons in Karnataka State Akkamahadevi Women’s University (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The aim of the research work was to find out the “Study on Emotional intelligence and Self-confidence among Sports Person and Non-Sports Person of Karnataka State Akkamahadevi Women’s University”. For the purpose of the research study 200 University Female students in the age group of 19 to 25 years belonging to the students of Karnataka State Akkamahadevi Women’s University Sports Person and Non-Sports Person of Karnataka state were selected as subjects for the present study. The subjects were divided into Sports Person and Non-Sports Person. The Psychological variables selected for this study was such as The Psychological variables to measure Emotional intelligence standard questionnaire developed by Anukool Hyde and Sanjyot Pethe and Upinder Dhar and to assess Self- confidence standard questionnaire developed by M. Basavanna. The researcher’s data was gathered on Emotional Intelligence and Self-confidence variables and the same is described in the following table.